Moral Injury and Religiosity in US Veterans With Posttraumatic Stress Disorder Symptoms. Issue 5 (May 2018) - Koenig, Harold G.; Youssef, Nagy A.; Ames, Donna; Oliver, John P.; Teng, Ellen J.; Haynes, Kerry; Erickson, Zachary D.; Arnold, Irina; Currier, Joseph M.; O'Garo, Keisha; Pearce, Michelle
Abstract : Abstract: Moral injury (MI) involves feelings of shame, grief, meaninglessness, and remorse from having violated core moral beliefs related to traumatic experiences. This multisite cross-sectional study examined the association between religious involvement (RI) and MI symptoms, mediators of the relationship, and the modifying effects of posttraumatic stress disorder (PTSD) severity in 373 US veterans with PTSD symptoms who served in a combat theater. Assessed were demographic, military, religious, physical, social, behavioral, and psychological characteristics using standard measures of RI, MI symptoms, PTSD, depression, and anxiety. MI was widespread, with over 90% reporting high levels of at least one MI symptom and the majority reporting at least five symptoms or more. In the overall sample, religiosity was inversely related to MI in bivariate analyses ( r = −0.25, p < 0.0001) and multivariate analyses ( B = −0.40, p = 0.001); however, this relationship was present only among veterans with severe PTSD ( B = −0.65, p = 0.0003). These findings have relevance for the care of veterans with PTSD.